BARBERSHOP HARI INI : PERSPEKTIF PENERAPAN AKUNTANSI - Rauf, Abdul Rauf; Adella Fitri, Sri; Oktavia, Abel; Nabila, Aisyah; R, Ramadanis.; A, Aysyah.; Rahmi, Mega; Zubaidah, Dea; Fitria, Nita; Yuliani, Dila; Marlin, Khairul; Nirmala, Dina; Putri Utami, Elfina (Account: Jurnal Akuntansi, Keuangan dan Perbankan, 2023)
This study aims to be able to describe the procedures for making accounting records and financial reports on barbershop services that are in accordance with the accounting cycle, so that they have appropriate and correct financial reports to be given to certain parties or related parties who will later assist in developing and progressing their business. and facilitate decision making for barbershop service companies in the future as the basis for policies or business development strategies. The results of the research conducted by observing the location and conducting interviews related to the basic concept of recording which consists of 6 parts, the counter concept consists of 3 parts, the concept of business continuity consists of 3 parts, and the time period used consists of 3 parts. These four stages have an effect on making financial reports which will be very useful for businesses.